STRATEGI PEMBENTUKAN KARAKTER KRISTIANI PADA ANAK BERKEBUTUHAN KHUSUS - Elni Paembonan; Jeslin, Yustin Pangloli, Reti Pareallo, Grace Asari Pasinggi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Christian Character Formation in Children with Special Needs (ABK) is both a challenge and an important responsibility for families, schools, and churches. These children have unique needs that require a holistic, personalized, and inclusive approach. This literature study aims to identify effective strategies for instilling Christian values in ABK by highlighting the role of love, exemplary modeling, scripture-based learning, and collaboration between family, school, and church environments. Grounded in biblical principles, such as Proverbs 22:6 and Colossians 3:12-14, this article emphasizes the importance of an approach rooted in love, patience, and appreciation for the uniqueness of each child. This study also reveals challenges, such as differences in understanding levels and behaviors, and offers practical solutions that can be applied. Through targeted and appropriate strategies, ABK can grow into individuals who reflect Christian values while fulfilling their calling as children of God